Investigation of non-National Immunization Program vaccination intentions in rural areas of China - Xiuli Wang; Yaru Fan; Wei Wang (BMC, 2023)
Abstract Background China's current immunization program was revised in 2007. Some common childhood vaccines such as those for influenza, pediatric pneumonia, Haemophilus influenzae, varicella, and rotavirus have not been included in the National Immunization Program (NIP) and need to be purchased by children's guardians at their own expense. Rural areas, constrained by economic development and vaccine awareness, have a low non-NIP vaccination rate and more family medical expenses and social burden. This study aims to examine the awareness and attitude of rural parents about non-NIP vaccines and relevant factors influencing their vaccination intention to provide strategic suggestions for expanding and improving the Chinese government's NIP policy. Methods A qualitative method of in-depth interviews were conducted for this study. We interviewed 30 rural parents in a central Chinese village to investigate their awareness of non-NIP vaccines and their vaccination intention and behavior. All the interview data were analyzed through the Colaizzi seven-step data analysis method. Results This study summarized the individual and social level factors influencing the non-NIP vaccination intention of rural parents. The individual level factors include four themes: perceived severity with physical harm, treatment consumption (cost of the treatment of the subject diseases), psychological burden, and social consequences being subthemes; perceived vulnerability with age vulnerability, medical history, immune quality (children's underlying immune status), and environmental vulnerability (sanitary condition of the rural environment) as subthemes; perceived efficacy with effect perception, psychological comfort, protective strength, and functional compensation (functions of non-NIP vaccines unreplaceable by NIP vaccines) being subthemes; and perceived cost consisting of two subthemes cost burden and adverse reaction. The social level influencing factors include the vaccination opinions in rural social networks, the accessibility of health services and vaccine products, and the guidance and promotion of vaccination policies. These factors act outside of individuals' subjective awareness and influence decisions regarding non-NIP vaccination in rural areas. Conclusion Based on these influencing factors, this study constructs a structural model for non-NIP vaccination decision-making process in rural areas of China. The results play a guiding role in directing attention to children's health, promoting non-NIP vaccination, facilitating the dissemination of vaccine knowledge in rural areas, and improving NIP policies and practices in China.